PRACTICAL IMPLEMENTATION OF OPTIMAL CONTROL POWER FLUX MUTUAL PAYMENT OF ELECTRIC NETWORKS WITH CROSS-TRANSFORMER - Lezhniuk, P. D.; Rubanenko, O. Ye.; Kylymchuk, A. V. (Visnyk of Vinnytsia Politechnical Institute, 2016)
There has been considered the problem of reducing the additional active power losses caused by mutual and transit overflows of power mains, by determining the optimal location of the cross angle of the transformer and its networks at download an example test circuit IEEE 230/138 kV. The technical and economic effect of setting a cross-transformer to the electric grid has been estimated.